Polskie poligony w aspekcie realizowanych działań militarnych i rekultywacji terenów popoligonowych - Borucka, Anna; Mikosz, Bogusław (Leśne Prace Badawcze, 2012)
Although training activities in military training grounds are required to ensure the sovereignty of a country, their effect on the environment can nevertheless moderated be effective management. The ongoing preparation of soldiers by the army to accomplish tasks under combat conditions should be reconciled with environmental protection in military training grounds. This requires a constant compromise between environmental protection and military training and activities. It is possible for training to be organised in such a way that its negative influences on the natural environment are minimised. However training practices that are sympathetic to the natural environment are yet to be implemented in Poland. This has resulted in training areas devastated by heavy military equipment, toxic combat substances, and combat simulations – many of which have been transferred to the National Forests for bioremediation to repair the damage caused to the environment. The task of successful reclamation of these areas demands great financial and human resources and the devotion of considerable effort and planning.